Philanthropic giving in Singapore: The tax landscape - OOI, Vincent (Institutional Knowledge at Singapore Management University, 2023)
This article sets out the tax landscape for philanthropic giving in Singapore in detail. Notably, Singapore recently enacted a new s 10J that governs appropriations of trading stock for purposes outside the ordinary course of business (which might be seen as somewhat of a codification of the rule in "Sharkey v Wernher"). There are now provisions which apply specifically to donations of trading stock, which should be considered when donations in kind are contemplated.The article also covers the use of donor-advised funds ("DAFs"). The tax consequences of using a DAF for philanthropic structuring are discussed, explaining that it is well possible to receive the tax benefits from charitable donations immediately, even if one has not yet found a worthy cause to donate to.The article concludes by noting that the Singapore government has indicated that it is currently reviewing its tax incentive schemes in order to make Singapore more attractive. It is likely that part of this review would involve relooking at the current rules on donations channeled to foreign charitable causes, which may be relaxed to some extent moving forward